Online educational counselling for students with special needs: building rapport - Debenham , Margaret; Whitelock , Denise M.; Fung , Pat; Emms , Judy M. (Research in Learning Technology)
Distance learners with long-term health problems face a number of difficulties in their studies. These include severe fatigue, problems of manual dexterity, academic and social isolation, together with a need for better interactive communication with support agencies (Debenham, 1996a). It was expected that the use of computer-mediated communication (CMC) could provide a possible way to tackle all four problems described above. DOI:10.1080/0968776990070104